Boosting the ultra-stable unencapsulated perovskite solar cells by using montmorillonite/CH3NH3PbI3 nanocomposite as photoactive layer. Issue 4 (10th December 2018) - Huang, Hsin-Hsiang; Shih, Yen-Chen; Wang, Leeyih; Lin, King-Fu
Abstract : The exMMTs, formed as a shell on top of CH3 NH3 PbI3 perovskite crystals, achieve ultra-stable unencapsulated PSCs. Abstract : The power conversion efficiency of the perovskite solar cell is high enough to be commercially viable. However, long-term stability is the inevitable issue that obstructs its commercialization. Here, we demonstrate that the half-year (∼4680 h) stable unencapsulated inverted solar cell has almost zero loss in performance, measured under controlled environmental condition, when using montmorillonite (MMT)/CH3 NH3 PbI3 nanocomposite as photoactive layer. It yields up to 17.29% in power conversion efficiency, owing to the formation of an outstandingly dense gas permeation barrier of exfoliated MMT shell that effectively retards the moisture from penetrating into the perovskite. It is believed that this extensively modified device and low-cost architecture will compellingly lead to the timely commercialization of perovskite solar cells.